The Impact of Health Quality and Pollution Levels on Tourist Arrival: A Case Study of Six ASEAN Countries, 2010-2022 - Putra, Devarra Anggara; Dewanti, Diah Setyawati (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This research aims to analyze the impact of health quality and pollution levels on tourist flows in six ASEAN countries during the period of 2010-2022. Health quality is measured based on life expectancy, population growth, and COVID-19, while pollution levels are assessed using the concentration of PM2.5 particles in the air. Data was obtained from reliable sources and analyzed using a panel data regression model. The method used in this research is panel data analysis with a common effects, fixed effects, and random effects approach to test the relationship between variables. The approach chosen in this research is the general effects. Research results show that better health quality and lower pollution levels significantly increase the number of tourists visiting these countries. Research shows that health quality has a significant positive impact on tourist flows, while pollution levels have a significant negative impact. This finding shows that improving health quality and reducing pollution levels can encourage an increase in tourist flows. Thus, governments in ASEAN countries need to pay attention to health factors and design strategies to enhance the tourism sector by improving health quality and managing pollution.